1997
DOI: 10.1038/sj.bmt.1700986
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the expression of Fas/Fas-ligand and the lymphocyte subset reconstitution according to the occurrence of acute GVHD

Abstract: Summary:mechanisms mediated by cytokines released from donorderived T cells. 1,2 Therefore, more detailed identification of T cell subsets can be an exceptionally good way to eluciAcute graft-versus-host disease (aGVHD) remains a major barrier to a wider application of allogeneic bone date the immune mechanism responsible for aGVHD. Recently accumulating evidence indicates that the Fas marrow transplantation (BMT). Although this complication is mainly dependent on donor-derived T lympho-(APO-1; CD95)/Fas-ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 1 publication
(2 reference statements)
1
12
0
1
Order By: Relevance
“…Presently, only a few groups have analyzed immune transcript levels in humans after SCT. 15,16 In agreement with our hypothesis that acute GVHD is associated with the expression of a specific subset of immune activation genes, we determined that acute GVHD might be associated with an upregulation of the gene expressions of granzyme B, perforin and FasL. In the study, increased levels of these genes were detected in five out of five patients diagnosed with acute GVHD.…”
Section: Gene Expression and Plasma Concentrationssupporting
confidence: 73%
See 1 more Smart Citation
“…Presently, only a few groups have analyzed immune transcript levels in humans after SCT. 15,16 In agreement with our hypothesis that acute GVHD is associated with the expression of a specific subset of immune activation genes, we determined that acute GVHD might be associated with an upregulation of the gene expressions of granzyme B, perforin and FasL. In the study, increased levels of these genes were detected in five out of five patients diagnosed with acute GVHD.…”
Section: Gene Expression and Plasma Concentrationssupporting
confidence: 73%
“…10 Several studies have also demonstrated the importance of the FasL and perforin pathways, as well as the TNF-a expression (or secretion) for the development of acute GVHD. [11][12][13][14][15][16] However, FasL, granzyme B, perforin and TNF-a gene expression in acute GVHD has not been further evaluated in stem cell transplanted patients, and its clinical significance remains to be elucidated in humans.…”
mentioning
confidence: 99%
“…14 In addition, an increase in the percentage of CD8 + cells which express FasL in patients with aGVHD has been demonstrated. 15 The relationship between the Fas/FasL system and the development of aGVHD is complex. Activated Fas/FasL system may be responsible for the tissue damage associated with aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The effector mechanisms that have been studied include the Fas/Fas ligand (FasL), perforin/granzyme, and TRAIL/DR5 pathways and several cytokines, including TNF-␣ and IFN-␥ (2). Aside from differences in the results of several experimental models, most studies indicate an important role for Fas/FasL in systemic and liver GVHD (3)(4)(5), while TNF-␣ seems to be involved in intestinal GVHD (6 -8). Conversely, different pathways have been described in GVL activity.…”
mentioning
confidence: 99%
“…A llogeneic bone marrow transplantation (allo-BMT) 3 is an effective therapeutic strategy for hematological malignancies. Its therapeutic efficacy could be enhanced by facilitating the capacity of donor T cells to react against tumor cells, i.e., graft-versus-leukemia (GVL) effect, while avoiding graft-versus-host disease (GVHD), the primary complication of this therapy (1).…”
mentioning
confidence: 99%